A influência das folksonomias na eficiência da fase inicial de modelagem conceitual - Pinheiro, Josiane Melchiori (2016)
This study examines the hypothesis that using folksonomies induced from collaborative tagging systems in conceptual modeling should reduce the number of divergences between actors when they elicit terms to be used in a model, using as baseline terms extracted from webpages based on term frequency. It uses as efficiency measure the number of divergences, because the fewer the divergences, the less time and effort required to create a conceptual model. It describes the controlled conceptual modeling experiments that were performed using experimental groups that received a folksonomy and control groups that received terms extracted from webpages. The results show that the experimental and control groups obtained similar numbers of divergences. Other efficiency measures, such as reuse of terms in the phases of conceptual modeling and perceived ease of performing the modeling task, confirmed the results obtained by the number of divergences, with slightly greater efficiency among the experimental groups.